Neonatal systemic inflammation and the risk of low scores on measures of reading and mathematics achievement at age 10 years among children born extremely preterm - Leviton, Alan (Int J Dev Neurosci, 2018)
BACKGROUND: Difficulties with reading and math occur more commonly among children born extremely preterm than among children born at term. Reasons for this are unclear. METHODS: We measured the concentrations of 27 inflammatory-related and neurotrophic/angiogenic proteins (angio-neurotrophic proteins) in multiple blood specimens collected a week apart during the first postnatal month from 660 children born before the 28(th) week of gestation who at age 10 years had an IQ ≥ 70 and a Wechsler Individual Achievement Test 3(rd) edition (WIAT-III) assessment. We identified four groups of children, those who had a Z-score ≤ −1 on the Word Reading assessment only, on the Numerical Operations assessment only, on both of these assessments, and on neither, which served as the referent group. We then modeled the risk of each learning limitation associated with a top quartile concentration of each protein, and with high and lower concentrations of multiple proteins. RESULTS: The protein profile of low reading scores was confined to the third and fourth postnatal weeks when increased risks were associated with high concentrations of IL-8 and ICAM-1 in the presence of low concentrations of angio-neurotrophic proteins. The profile of low math scores was very similar, except it did not include ICAM-1. In contrast, the profile of low scores on both assessments was present in each of the first four postnatal weeks. The increased risks associated with high concentrations of TNF-α in the first two weeks and of IL-8 and ICAM-1 in the next two weeks were modulated down by high concentrations of angio-neurotrophic proteins. CONCLUSIONS: High concentrations of angio-neurotrophic proteins appear to reduce/moderate the risk of each learning limitation associated with systemic inflammation. The three categories of limitations have protein profiles with some similarities, and yet some differences, too.